E-Module Based on Augmented Reality Media on Magnetic Materials - Afsas, Siti Khodijah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to develop e-modules based on Augmented Reality media and determine their effectiveness. The research method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). Data collection techniques with documentation, interview, questionnaire, and test methods. The population for this study comprised students from SMPN 40 Semarang, totaling 62 students. The sample size consisted of 31 students. Using a random sampling technique. The data analysis technique used is the t-test to assess the effectiveness of the developed e-module. Data collection instruments through expert validation sheets and student readability test sheets. The validation results of material experts amounted to 93.70%, media experts amounted to 92.01% with very valid criteria, and supported by student readability tests of 83.76% with excellent criteria. The results of Augmented Reality-based E-module research have characteristics, namely digital form utilizing Augmented Reality applications, 3D image display is interactive and contains magnetic material sub-material magnetic material. The results of the effectiveness test with a pre-test completeness percentage of 64,5% and 90,3% proved that there was an increase so that Augmented Reality-based e-modules can be used as teaching materials in science learning on magnetic material sub materials.